The effect of g-jitter on double diffusion by natural convection from a sphere - Shafie, Sharidan; Amin, Norsarahaida; Pop, Ioan (Elsevier Ltd, 2005)
This paper specifically considers the generation of steady streaming induced by g-jitter on double diffusion from a sphere immersed in a viscous and incompressible fluid. The governing equations of motion are first written in dimensionless forms and the resulting equations obtained after the introduction of the stream function are solved analytically and numerically. Analytical results using the matched asymptotic method are presented for the case when the Reynolds number, Re, is small (Re 1), while numerical results using the Keller-box method are given for (Re 1), or the boundary layer approximation. Both the cases of assisting and opposing thermal and concentration buoyancies are considered. Table and graphical results for the skin friction and heat and mass transfer from the sphere are presented and discussed for various parametric physical conditions. It is shown that for opposing buoyant forces the skin friction and heat and mass transfer rates follow complex trends depending on the buoyant ratio parameter, Prandtl and Schmidt numbers